Intensification of convective heat transfer and heat exchanger performance by the combined influence of a twisted tube and twisted tape - P. Samruaisin; S. Kunlabud; K. Kunnarak; V. Chuwattanakul; S. Eiamsa-ard (My University, 2019)
Twisted tubes and twisted tapes are swirl flow generators utilized for increasing thermal performance. The combined effects of twisted tubes and twisted tapes on heat transfer, pressure drop and thermal performance were experimentally investigated. Experiments were performed using a trapezoidal shaped twisted tube and twisted tapes having various twist ratios (y/w = 2.0, 3.0, 4.0 and 5.0). Water was used as the test fluid in a turbulent regime (4500 < Re < 16,000). A simulation of velocity, temperature contours and local Nusselt number plots was also performed to gain information about fluid flow and heat transfer. The results of the combined devices are studied with those of a smooth circular tube and a twisted tube alone, for comparison. The experimental results show that at a given Re, the Nusselt number (Nu), friction factor (f) and thermal performance of a twisted tube mounted with a twisted tape are consistently higher than those of the twisted tube alone and a smooth circular tube. Additionally, the heat transfer, friction loss and thermal performance factor increase with a reduction of the twist ratio (y/w) since the tape with a smaller y/w gives stronger and more consistent swirl flow.
Keywords: Heat transfer enhancement; Enhanced heat transfer; Heat Transfer Mechanisms